Globalization and female economic participation in MINT and BRICS countries - Tolulope T. Osinubi; Simplice Asongu (African Governance and Development Institute (AGDI), 2020)
This study examines the effect of globalization on female economic participation (FEP) in MINT (Mexico, Indonesia, Nigeria & Turkey) and BRICS (Brazil, Russia, India, China & South Africa) countries between 2004 and 2018. Four measures of globalization are employed and sourced from KOF globalization index, 2018, while the female labour force participation rate is a proxy for FEP. The empirical evidence is based on Pooled Mean Group (PMG) estimators. The findings of the PMG estimator from the Panel ARDL method reveal that political and overall globalization in MINT and BRICS countries have a positive impact on FEP, whereas social globalization exerts a negative impact on FEP in the long-run. It is observed that economic globalization has no long-run effect on FEP. Contrarily, all the measures of globalization posit no short-run effect on FEP in the short-run. This supports the argument that globalization has no immediate effect on FEP. Thus, it is recommended that both MINT and BRICS countries should find a way of improving the process of globalization generally to empower women to be involved in economic activities. This study complements the extant literature by focusing on how globalization dynamics influence FEP in the MINT and BRICS countries.
Keywords: E60; F40; F59; D60; 330; Globalization; female; gender; labour force participation; MINT and BRICS countries